The thinkers of freedom (or a universe hidden between loose papers) - Gómez Híjar, Beltrán (2021)
In the history of economic and political thought, there is a diversity of authors who have different interpretations of human nature, institutions, and of how society should be organized. Among these authors, there is one branch, formed by the thinkers of the Austrian School of Economics, who, in addition to their great contributions to economic thought, also made a transcendental incursion into other disciplines, such as philosophy, political science, law, among others. These thinkers, in turn, are part of a larger group: that of the philosophers of freedom, that is, of those thinkers who intelectually defended individual freedomagainst arbitrary coercion of a third party, especially the State.